2014
DOI: 10.5624/isd.2014.44.2.149
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of a pre-procedural mouthrinse in reducing bacteria on radiographic phosphor plates

Abstract: PurposeThis study assessed the effectiveness of three antimicrobial mouthrinses in reducing microbial growth on photostimulable phosphor (PSP) plates.Materials and MethodsPrior to performing a full-mouth radiographic survey (FMX), subjects were asked to rinse with one of the three test rinses (Listerine®, Decapinol®, or chlorhexidine oral rinse 0.12%) or to refrain from rinsing. Four PSP plates were sampled from each FMX through collection into sterile containers upon exiting the scanner. Flame-sterilized forc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 20 publications
1
8
0
Order By: Relevance
“…There have been some studies that have shown the potential use of chlorhexidine gargle and gas sterilization for infection control. 10,12 In summary, this study proved that there are statistical differences in perforation rates according to the applications of the intraoral barriers. The use of a double barrier can reduce the perforation rate by more than half as compared with the use of a single barrier.…”
Section: Discussionsupporting
confidence: 55%
“…There have been some studies that have shown the potential use of chlorhexidine gargle and gas sterilization for infection control. 10,12 In summary, this study proved that there are statistical differences in perforation rates according to the applications of the intraoral barriers. The use of a double barrier can reduce the perforation rate by more than half as compared with the use of a single barrier.…”
Section: Discussionsupporting
confidence: 55%
“…• antiseptic rinsing before treatment [19][20][21][22] • use of dental rubber dam [16,23,24] • high-volume evacuation (HVE) suction device [14,15,[25][26][27] or other dry-field isolation systems such as the "Isolite-system" [28] • Barrier protection: mask, glove, eye protection goggle, protection shield [29] • High-efficiency particulate air room filters…”
Section: Plos Onementioning
confidence: 99%
“…Free radicals released by hydrogen peroxide break the electron-rich alkene double bonds which are responsible for discoloration, resulting in stain removal. [6] The use of hydrogen peroxide as an adjunct to chlorhexidine has been found to be very effective in reducing plaque scores and in preventing the stain development. [7] Several studies have been conducted in the past on preprocedural rinsing using a variety of methods; however, so far, none of the studies have compared the efficacy of CHG and hydrogen peroxide in reducing the aerosolized bacterial contamination.…”
Section: Introductionmentioning
confidence: 99%